IMITATIVE METHODS IN FOREIGN LANGUAGE TEACHING (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the significance of imitation in foreign language teaching. The author compares imitative and non-imitative pedagogical approaches, analyzing their functions in the educational process and evaluating their impact on students’ language acquisition outcomes.
Keywords: interactive approaches; foreign language teaching; linguistics; pedagogy; imitation; imitative techniques